Leer Balún-Canán sin abrir el libro: la bibliografía material en el análisis de la obra literaria - Higashi, Alejandro (El Colegio de México, 2013)
In this article, the author focuses on the role of Bibliography in buildinghermeneutic strategies for the modern mexican literary studies.If the Bibliography is the academic study of books as physical and culturalobjects, we can expect that the bibliographical analysis explainswith details the historical first reception of the literary work. In orderto explain this point, the careful analysis of Balún-Canán’s first editionoffers us a new vision of its influence, as material and cultural object,on its first critical reception.